Accountability of Palm - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The problem of the environment is a serious issue that must be addressed by the government and the community as a supervision and reporter of each of the activities of the destroyer of the environment. The pollution and environmental damage continue to increase in line with the increased industrial activity or similar substances; surely the situation needs to get the protection of the law. The pollution or environmental damage, mostly in the context of running a commercial business and often is also the attitude of rulers and the entrepreneurs who do not run or neglecting the obligations of their obligations in the management of the environment. This research is a descriptive quantitative i.e. with provides an overview of the company that takes the environment around the enterprise. Data collection method in this investigation using bibliographical study (Library Research).